Disparities in socio-economic status and BMI in the UK are partly due to genetic and environmental luck - Casper A.P. Burik; Hyeokmoon Kweon; Philipp D. Koellinger (Tinbergen Institute, 2021)
Two family-specific lotteries take place during conception— a social lottery that determines who our parents are and which environment we grow up in, and a genetic lottery that determines which part of their genomes our parents pass on to us. The outcomes of these lotteries create inequalities of opportunity that can translate into disparities in health and socioeconomic status. Here, we estimate a lower bound for the relevance of these two lotteries for differences in education, income and body mass index in a sample of 38,698 siblings in the UK who were born between 1937 and 1970. Our estimates are based on models that combine family-specific effects with gene-by-environment interactions. We find that the random differences between siblings in their genetic endowments clearly contribute towards inequalities in the outcomes we study. Our rough proxy of the environment people grew up in, which we derived from their place of birth, are also predictive of the studied outcomes, but not beyond the relevance of family environment. Our estimates suggest that at least 13 to 17 percent of the inequalities in education, wages and BMI in the UK are due to inequalities in opportunity that arise from the outcomes of the social and the genetic lottery.
Keywords: I24; I14; J00; 330; inequality; income; education; BMI; genetics; polygenic index